2018
DOI: 10.1038/pr.2018.52
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolites of volatile organic compounds of infants in the neonatal intensive care unit

Abstract: BackgroundPreterm infants (PTI) in the NICU are often placed in incubators that may increase their exposure to volatile organic chemicals (VOCs). To determine whether PTI in incubators have higher urinary concentrations of VOC metabolites compared with infants in cribs.MethodsUrine from 40 PTI in incubators and 40 infants in cribs was collected and analyzed for 28 urinary VOC biomarkers. Differences in metabolite concentrations between the two groups were compared.ResultsTwenty two of the VOC metabolites were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In the past decade, metabolic research has pointed to new potential biomarkers for various medical conditions, including oncologic, inflammatory, endocrine, and infectious diseases in both adults and children [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The sensitivity of a metabolomics approach to detect subtle alterations in metabolic pathways can, in addition, provide insight into mechanisms underlying various (patho)physiological conditions [33].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, metabolic research has pointed to new potential biomarkers for various medical conditions, including oncologic, inflammatory, endocrine, and infectious diseases in both adults and children [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The sensitivity of a metabolomics approach to detect subtle alterations in metabolic pathways can, in addition, provide insight into mechanisms underlying various (patho)physiological conditions [33].…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated by El-Metwally [30], the link between VOCs measures and their potential role as a disease biomarker may be confounded by differential environmental exposures or pre-emptive therapeutic interventions. Preterm infants in particular are at high risk of absorbing environmental compounds, and have immature secretory and excretory pathways.…”
Section: Limitations Of Current Methodsmentioning
confidence: 99%
“…There have been several papers examining the detection of peptide compounds in urine to assist with the early diagnosis of NEC [29], but very little attention has been paid to examining VOCs in urine for early diagnostics. A study by El-Metwally [30] compared VOC metabolites in the urine of preterm infants nursed in incubators compared to open cots using ultra-high-performance liquid chromatography coupled with electrospray ionization tandem MS. They demonstrated that detecting these metabolites was possible and that there was a significant difference in the VOC metabolites between incubator-and cot-nursed infants.…”
Section: Vocs In Neonatal Urinementioning
confidence: 99%
“…[23,24] In support of the ubiquity of VC exposure, a recent study indicated that neonates have already adult exposure levels to VC and other VOCs. [25] Owing to its widespread presence and its known potential human risk, VC is ranked #4 on the ATSDR Hazardous Substance Priority List. [26] Exposure to some anthropogenic chemicals is associated with increased HCC risk, including VC.…”
Section: Introductionmentioning
confidence: 99%